The tuning of TiO2-Al2O3 composite support for the fabrication of PtSn-based catalysts with superior catalytic performance in the propane dehydrogenation. (March 2021) - Wang, Guangjian; Song, Ning; Lu, Kai; Zhang, Qinqin; Fu, Haitao; Bing, Liancheng; Wang, Fang; Wang, Fengzhong; Han, Dezhi
Graphical abstract: Abstract: Low-carbon olefins are considered as important chemical building blocks for the synthesis of various chemicals. Many pioneer works have developed novel processes or catalysts for satisfying their steadily increased demand. In this study, the PtSn-based catalysts were prepared by the TiO2 -Al2 O3 composite supports for the subsequent catalytic tests in the propane dehydrogenation (PDH) reaction. The prepared supports and corresponding catalysts were intensively characterized by X-ray diffraction (XRD), low-temperature N2 adsorption-desorption, high-resolution transmission electron microscopy (HRTEM), NH3 temperature-programmed desorption (NH3 -TPD), and H2 temperature-programmed reduction (H2 -TPR), etc. The results of catalytic tests and characterizations revealed that the high dispersion of Pt, the proper acidity, and the enhanced metal-support interaction were responsible for the improved catalytic performance over the prepared catalysts in PDH reaction. Especially, the catalyst prepared with 20 wt.% TiO2 -Al2 O3 composite support exhibited the stable and highest propylene selectivity (>88 %) under the investigation time.